The doctrine of consideration in english contract law and related legal constructions in the law of countries of the romano-german legal family - Valentyna Skrypnyk (Вісник Харківського національного університету імені В. Н. Каразіна Серія: «Право», 2022)
Introduction. The article is devoted to the doctrine of consideration in Anglo-American law and similar legal constructions in the law of the countries of the Romano-Germanic legal family. On the basis of foreign studies of the doctrine of consideration, the author finds out the legal nature of this doctrine in contract law. Attention is focused on the fact that consideration is associated with the categories of interest, good, benefit, benefit, loss. It is indicated that consideration is an essential condition for the validity of any contract, including an informal one. An attempt is made to compare the doctrine of consideration with the concept of cause of transaction in the RomanoGermanic legal family, which was developed due to the reception of Roman law.